The Life of Sherman Coolidge, Arapaho Activist - Lewandowski, Tadeusz, 1973- (Book collections on Project MUSE., 2022)
"Sherman Coolidge's (1860-1932) panoramic life as survivor of the Indian wars, witness to the maladministration of the reservation system, mediator between Native and white worlds, and ultimate defender of Native rights and heritage make him the literal embodiment of his era of American Indian history"--